Finance and Development, June 1965. (Finance and Development; Finance and Development ;, 1965)
This paper analyzes the effect of rapid inflation on a country's international position. The paper highlights that when prices and costs in any country rise rapidly, goods produced in the country soon become more expensive than similar goods produced abroad. Unless the exchange rate changes, this encourages imports and discourages exports. As prices in a country rise more rapidly than in the rest of the world, individuals in that country tend to turn from buying these increasingly expensive products of their own industries to the relatively cheaper foreign goods.